Energy expenditure of the whole body electromyostimulation: A comparison which other physics activities, methods and training devices - De La Cámara, Miguel Ángel (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2016)
Personal trainings with integrated electro-stimulation devices or Whole Body Electromyostimulation (WB-EMS) have multiplied in Spain and Central Europe. WB-EMS centers pose benefits for the training with this device, as a high-energy expenditure compared to other physical activities. In some cases one gets to match 20 minutes from WB-EMS with 3 hours of intense exercise. A literature review was conducted to compare the energy costs generated by a session of WB-EMS and other activities, methods or training devices. The results show that, at similar intensity, a session of WB-EMS as described in the study, not presents be superior to other activities. This publicity can change the type or frequency of activities of some users, who, motivated by the advertised benefit, could leave or reduce them, with the consequent risk of not to accumulate the minimum of physical activity recommended by the American College of Sports Medicine or the World Health Organization.